2006
DOI: 10.1111/j.1525-142x.2006.05070.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and functional analysis of the tailless enhancer in Musca domestica and Drosophila melanogaster

Abstract: To further understand the evolutionary dynamics of the regulatory interactions underlying development, we expand on our previous analysis of hunchback and compare the structure and function of the tailless enhancer between Musca domestica and Drosophila melanogaster. Our analysis shows that although the expression patterns and functional protein domains of tll are conserved between Musca and Drosophila, the enhancer sequences are unalignable. Upon closer investigation, we find that these highly diverged enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Moreover, even when the enhancer sequences are conserved, the enhancers themselves may occupy different positions in relation to the gene that is regulated and, therefore, may not be detected in alignments of large DNA segments. For example, comparisons of the housefly and fruitfly, showed that even though the domain of tll expression is conserved, the enhancer sequences that direct expression cannot be aligned, and neither the sequence of the enhancer nor the sequence, number, spacing and position of the binding sites that direct expression are conserved (Wratten et al, 2006). Therefore, it is perhaps not surprising that there are no alignable regions of upstream engrailed DNA between amphioxus and C. intestinalis even though both genes are expressed in the CNS.…”
Section: Sequence Alignments Over Wide Phylogenetic Distances Can Revmentioning
confidence: 97%
“…Moreover, even when the enhancer sequences are conserved, the enhancers themselves may occupy different positions in relation to the gene that is regulated and, therefore, may not be detected in alignments of large DNA segments. For example, comparisons of the housefly and fruitfly, showed that even though the domain of tll expression is conserved, the enhancer sequences that direct expression cannot be aligned, and neither the sequence of the enhancer nor the sequence, number, spacing and position of the binding sites that direct expression are conserved (Wratten et al, 2006). Therefore, it is perhaps not surprising that there are no alignable regions of upstream engrailed DNA between amphioxus and C. intestinalis even though both genes are expressed in the CNS.…”
Section: Sequence Alignments Over Wide Phylogenetic Distances Can Revmentioning
confidence: 97%
“…Early studies included those on Caenorhabditis and vertebrates, in which it was noticed that interspecific differences in expression profiles can be the result of changes in the regulatory sequences upstream of particular genes critical during development (Belting et al, 1998;Wang and Chamberlin, 2002). These changes in gene expression can be due to de novo evolution of regulatory sequences (Gonzalez et al, 1995;Papaceit et al, 2004;Wratten et al, 2006), although a large number of studies indicate that their evolution often involves the rearrangement and modification of sequences with known regulatory roles (Gompel et al, 2005;Prud'-homme et al, 2006). In several cases, mutations in cisregulatory sequences imply gains or losses of binding sites for key selector genes in a lineage-specific manner leading to complex changes in the patterns of gene expression.…”
Section: The Genetic Bases Of the Evolution Of Gene-expression And Trmentioning
confidence: 99%
“…Another example comes from the study of the Bicoid (Bcd)-binding sites in the upstream of the genes hunchback (hb) and tailless (tll) of D. melanogaster and the house fly Musca domestica. This study combined transgenics with in vitro binding assays to provide one of the first comparative measures of the extent of regulatory incompatibility between species (Shaw et al, 2002;Wratten et al, 2006). There is not only evidence for coevolution between the trans-and cis-regulatory elements, but also evidence that the incompatibility does not result in a reduced binding, but rather higher affinity.…”
Section: Evidence Of Ris From Studies On Gene Transfermentioning
confidence: 99%
“…And finally, there have been few detailed functional studies of CRE evolution. Most studies have focused on the functional conservation of CREs (18)(19)(20). Until very recently, there have been very few direct empirical examples linking CRE evolution to morphological evolution (21,22).…”
mentioning
confidence: 99%